Breastfeeding versus artificial feeding in the colombian context - Izzedin-Bouquet de Durán, Romina (2011)
At first, the article describes the nutritional and immunological benefits of breastfeeding for then to report on its status in the international and Colombian context by comparing it with his major competitor milk formula. Finally, the article shows the strategies that promote breastfeeding aiming to raise awarness about the commitment that we have as individuals and society with regard to maternal and child health.